State intervention and tourism business resilience: Exploring firm-level crisis responses - Joo-Ee Gan; Joann P. S. Lim; Alexander Trupp; Wai Ching Poon (Annals of Tourism Research Empirical Insights, 2024)
Business resilience and government intervention are critical in navigating crises. Guided by resilience theory and concepts of state intervention in global crises, this article examines firm-level strategies to the Covid-19 pandemic. The qualitative findings decipher adaptive resilience and business survival strategies concerning cashflow management, human resource management, management of current liabilities, asset management, and alternative business avenues. Government intervention included financial assistance, wage subsidy, loan moratorium, and other stimulus measures. Findings reveal mixed responses, highlighting the need for tailored and effective government intervention. The study extends resilience theory by integrating state intervention as an external driver of adaptive resilience, thereby providing a holistic understanding of resilience in crises. Practical implications provide policy-makers with insights on more effective crisis response strategies.
Keywords: 330; Adaptive resilience; Crisis management; Economic stimulus; Government intervention; Malaysia; Tourism business